The Issue Of Image In Fiction Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article provides detailed information about the role of music in the formation of the minds of schoolchildren, the methods and methods of effective organization of music culture classes in secondary schools.